Antibiotics in palliative medicine-results from a prospective epidemiological investigation from the HOPE survey - Stiel, Stephanie; Krumm, Norbert; Pestinger, Martina; Lindena, Gabriele; Nauck, Friedemann; Ostgathe, Christoph; Radbruch, Lukas; Elsner, Frank (Supportive Care in Cancer, 2012)
Background: Patients with advanced cancer are highly susceptible to infections. The decision whether to treat an active or suspected infection or to withhold or withdraw an antibiotic treatment in end-of-life care may be difficult. In order to quantify the antimicrobial prescribing practices and decision-making processes in palliative care units in Germany, a survey was performed as part of the Hospice and Palliative Evaluation in 2006. Method: With a specifically designed questionnaire, 448 patients for whom an active or suspected infection and antibiotic treatment was discussed were documented. Data on the use of and indication for antibiotic treatment and the decision-making on withdrawal or withholding of antibiotic therapy were collected. Results: 286 (63.8%) received an antibiotic therapy. In 88 cases, withdrawal of an ongoing treatment was documented. The most frequent reasons for withdrawal were: deterioration of general status (41.4%), inefficiency of therapy (25.7%), and explicit wish of patient (14.3%; multiple answers possible). Outcome of antimicrobial therapy was rated poor or very poor for a fifth of the cases and accordingly, antibiotics were more likely to be withdrawn if the clinical success was considered to be poor. The initiation of therapy was often decided by physicians solely, whereas withdrawing and withholding therapy demanded more often involvement of other team members in the decision-making process. Conclusion: The initiation of therapy seems to be easier than withdrawing and withholding, as involvement of other team members in the decision-making process was then sought more often. When antibiotics were given until death, the indication should be reconsidered because of a possibly undesirable prolongation of the dying process. Clinical practice may benefit from clear definitions of treatment goals and outcome criteria to better evaluate the necessity for and success of antimicrobial treatment. © 2011 Springer-Verlag.
Keywords: Antibiotics; Decision making; Indication; Palliative medicine; Therapy withdrawal; Therapy withholding